2018
DOI: 10.3390/ijms19041048
|View full text |Cite
|
Sign up to set email alerts
|

Transplantable Melanomas in Hamsters and Gerbils as Models for Human Melanoma. Sensitization in Melanoma Radiotherapy—From Animal Models to Clinical Trials

Abstract: The focus of the present review is to investigate the role of melanin in the radioprotection of melanoma and attempts to sensitize tumors to radiation by inhibiting melanogenesis. Early studies showed radical scavenging, oxygen consumption and adsorption as mechanisms of melanin radioprotection. Experimental models of melanoma in hamsters and in gerbils are described as well as their use in biochemical and radiobiological studies, including a spontaneously metastasizing ocular model. Some results from in vitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 192 publications
(259 reference statements)
1
36
0
Order By: Relevance
“…BHM melanotic Ma and SKMEL-188 cells show similar survival curves. Similar differences in response to radiation between BHM Ma and BHM Ab cells were reported for X ray irradiation, where pigmented cells (BHM Ma) were 2.4 times more radio resistant than the unpigmented (BHM Ab) ones [33]. In the case of proton radiation this characteristic is less pronounced but still marked with the ratio of mean lethal dose of 1.56.…”
Section: Resultssupporting
confidence: 63%
“…BHM melanotic Ma and SKMEL-188 cells show similar survival curves. Similar differences in response to radiation between BHM Ma and BHM Ab cells were reported for X ray irradiation, where pigmented cells (BHM Ma) were 2.4 times more radio resistant than the unpigmented (BHM Ab) ones [33]. In the case of proton radiation this characteristic is less pronounced but still marked with the ratio of mean lethal dose of 1.56.…”
Section: Resultssupporting
confidence: 63%
“…1,25(OH) 2 D 3 has antitumor properties affecting molecular pathways involved in proliferation, apoptosis and differentiation, but can also improve effectiveness of classical anticancer therapies (163,170). Experimental cell-and animal model-based data clearly showed that vitamin D and its analogs increased the effectiveness of well-known cancer chemotherapy drugs (such as doxorubicin, cisplatinum, gemcitabine and cyclophosphamide) (171-173).…”
Section: Vitamin D and Melanoma: Experimental And Clinical Evidencementioning
confidence: 99%
“…The clearest example of this is the increased spectrum of tumors observed in some GEM following exposure to carcinogens or radiation . Less popular rodent models in melanoma research, that is Syrian golden hamsters and Mongolian gerbils, are used for spontaneously occurring melanoma and for chemically induced melanoma, respectively . In particular, Syrian hamster, the Bomirski melanomas, consists of 5 transplantable in vivo‐variants and represent a good animal model for developing and testing potential melanoma vaccines .…”
Section: Introductionmentioning
confidence: 99%